Pengaruh Tingkat Kupon, Jenis SBN Ritel, Implementasi E-SBN, & Penurunan Nominal Pemesanan Terhadap Tingkat Partisipasi Investor Milenial SBN Ritel - Hendrocahyo Hendrocahyo (Jurnal Pasar Modal dan Bisnis, 2021)
In this research, we would like to seek the effectiveness of government strategy to attract millennial investors through a regression model. The strategies are lowering the minimum order and implementing online basis order (e-SBN). We also add variables such as coupon rate, and Government Bond Securities types, to test previous research conducted by Sylvié Formanka et.al (2019) related to the millennial decision-making process on investing. From our research, using cross-section linear regression method toward Government Retail Securities Bond from the year 2006 to 2019, we found that the coupon rate, the types of Government Securities Bond, the implementation of e-SBN, and the smaller amount of minimum order are having a significant influence toward the participation level of millennial investors.